A Preliminary Study on Computer Aided Process Planning for Generating Additive Manufacturing Products via 3D/4D/5D Printing - Izzah Nadhilah Ilias; Mohd Salman Abu Mansor (Engineering Proceedings)
This paper presents an integrated CAD/CAM system that can be used for Computer Aided Process Planning to interact or automate 3D/4D/5D printing process towards Industry 5.0. By creating a new algorithm, macro is developed that has the capability to determine any suitable type of printing process whether 3D, 4D or 5D printing for generating Additive Manufacturing products. The methodology of this study is focused starting from designing 3D CAD models for Additive Manufacturing products until generating 3D/4D/5D printing process planning by a creation of macro. The algorithm is tested by printing simulations from 3D printing extended up to 5D printing.